Konsentrasi Kepemilikan, Transaksi Pihak Berelasi, dan Kinerja Perusahaan - Pangesti, Nitami Galih; Hidayat, Widi (E-Jurnal Akuntansi; Vol 29 No 2 (2019), 2019)
Agency theory describe that ownership concentration is a good corporate governance system that helps to reduce agency problems arising from the divergence of interest between shareholders and managers. But, when ownership concentration becomes high, lead to another agency problem that is conflict between controlling shareholders and minority shareholders. This study purposed to examine the relation of ownership concentration and related party transactions on firm performance. This research uses quantitative descriptive method with associative approach. Sample used in this study was 474 manufacturing companies listed on the Indonesia Stock Exchange in 2014-2018. We used multiple linear regression as analysis technique. Results showed that ownership concentration had a positive effect on firm performance and related party transactions had a positive effect on firm performance. Keywords : Ownership Concentration; Related Party Transactions; Firm Performance.